Analysis of the Effectiveness of the Family Hope Program (PKH) in Improving Community Welfare in Sukorejo Village, Loceret District, Nganjuk Regency - Faizal Ansyori; Moch. Mahmudi Rosid; Durotun Nazilatus Saadah (CV. Civiliza Publishing, 2026)
This study aims to analyze the effectiveness of the Family Hope Program (PKH) in improving community welfare in Sukorejo Village, Loceret District, Nganjuk Regency in 2024. The study used a quantitative descriptive approach. The study population and sample consisted of 139 PKH beneficiary families, thus using a saturated sampling technique. Data were collected through questionnaires and analyzed using descriptive percentages to assess targeting accuracy, participant understanding, impact on children's education and health, fulfillment of basic needs, and program assistance. The results showed an overall effectiveness score of 80.2%, indicating that PKH implementation was running smoothly. The indicators with the highest achievement were the impact on children's education (88%) and recipient targeting accuracy (85%), while the lowest achievement was in the aspect of meeting basic family economic needs (69%). These findings indicate that PKH not only helps alleviate the burden of household expenses but also strengthens poor families' access to education and health services. Thus, PKH contributes positively to improving the welfare of beneficiary families in Sukorejo Village, although program socialization and the intensity of assistance still need to be strengthened.